The protrusive movement and the condyle path - the value of its registration - Alcantara, Ophelia; Mojica, Doris; Dominguez, Nanette (Adviser).
To determine the reability of the protrusive records as a means to establish condyle path and to establish a parameter in determining why (-) readings are obtained to complete denture service are the objectives of this study. Fifty subjects were used for this study. The horizontal condylar inclination was adjusted using protrusive records made in high heat wax. The adjustments were repeated three times for each subject as there were three observations done in each one of the fifty subjects. No significant difference was found in the three observations. The protrusive record was reproducible hence, it is valid and reliable.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.